Investigation of the antimicrobial properties of temperature-sensitive hydrogel containing silver sulfadiazine against various bacterial strains - Maha Mohammad AL-Rajabi; Teow Yeit Haan; Safa Senan Mahmod; Khalil Abdelrazek Khalil, (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
In burn wound management, infection poses a significant challenge, accounting for 75% of deaths in burn patients. Silver sulfadiazine is broadly used as an effective antibacterial agent for treating burns. Numerous researchers have explored various dosage forms of silver sulfadiazine, such as cream, ointment, topical spray, and hydrogel, for antimicrobial topical applications. Hydrogels offer appealing advantages over conventional drug delivery systems due to their sensitivity and responsiveness to stimuli, particularly temperature. Nevertheless, the comprehensive investigation of the antimicrobial properties of temperature-sensitive hydrogel containing silver sulfadiazine against different bacterial strains remains lacking. Thus, the main objective of the current study is to explore the antimicrobial properties of the temperature-sensitive hydrogel, incorporating silver sulfadiazine, against various bacterial strains colonized in burn wounds. To assess the antimicrobial activity of the temperature-sensitive hydrogel, inhibition zone diameters were measured against different types of Gram-positive strains (Staphylococcus aureus, Enterococcus faecalis, Enterococcus faecium, and Streptococcus pyogenes) and Gram-negative strains (Escherichia coli and Klebsiella pneumoniae). The synthesized silver sulfadiazine-loaded temperature-sensitive hydrogel exhibited remarkable antimicrobial efficacy against these bacteria. Notably, there was no significant difference in the inhibition zone diameter between the silver sulfadiazine-loaded temperature-sensitive hydrogel and the positive control (p>0.05). These findings affirm that the silver sulfadiazine-loaded temperature-sensitive hydrogel holds promise as a drug delivery medium, demonstrating excellent antimicrobial activity against various bacterial strains that colonized in burn wounds.